A proof‐of‐concept experimental study for vacuum‐driven anaerobic biosolids fermentation using the IntensiCarb technology. (3rd March 2022) - Okoye, Frances; Kakar, Farokh Laqa; Elbeshbishy, Elsayed; Bell, Kati; Muller, Christopher; Jimenez, Jose; Al‐Omari, Ahmed; Santoro, Domenico; Jang, Eunkyung; Walton, John; Bahreini, Gholamreza; Zaman, Masuduz; et al.
Abstract: This study demonstrates the potential of an innovative anaerobic treatment technology for municipal biosolids (IntensiCarb), which relies on vacuum evaporation to decouple solids and hydraulic retention times (SRT and HRT). We present proof‐of‐concept experiments using primary sludge and thickened waste activated sludge (50–50 v/v mixture) as feed for fermentation and carbon upgrading with the IntensiCarb unit. IntensiCarb fully decoupled the HRT and SRT in continuously stirred anaerobic reactors (CSAR) to achieve two intensification factors, that is, 1.3 and 2, while keeping the SRT constant at 3 days (including in the control fermenter). The intensified CSARs were compared to a conventional control system to determine the yields of particulate hydrolysis, VFA production, and nitrogen partitioning between fermentate and condensate. The intensified CSAR operating at an intensification factor 2 achieved a 65% improvement in particulate solubilization. Almost 50% of total ammonia was extracted without pH adjustment, while carbon was retained in the fermentate. Based on these results, the IntensiCarb technology allows water resource recovery facilities to achieve a high degree of plant‐wide intensification while partitioning nutrients into different streams and thickening solids. Practitioner Points: The IntensiCarb reactor can decouple hydraulic (HRT) and solids (SRT) retention times in anaerobic systems while also increasing particulate hydrolysis and overall plant capacity. Using vacuum as driving force of the IntensiCarb technology, the system could achieve thickening, digestion, and partial dewatering in the same unit—thus eliminating the complexity of multi‐stage biosolids treatment lines. The ability to partition nutrients between particulate, fermentate, and condensate assigns to the IntensiCarb unit a key role in recovery strategies for value‐added products such as nitrogen, phosphorus, and carbon, which can be recovered separately and independently. Abstract : Intermittent feed and vacuum extraction with the IntensiCarb reactor provide an avenue to recover water and volatile organics, while minimizing reactor volume.